2007
DOI: 10.1155/2007/78171
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Memory and Anxiety: From Genes to Behavior

Abstract: Interaction of anxiety and memory represents an essential feature of CNS functioning. This paper reviews experimental data coming from neurogenetics, neurochemistry, and behavioral pharmacology (as well as parallel clinical findings) reflecting different mechanisms of memory-anxiety interplay, including brain neurochemistry, circuitry, pharmacology, neuroplasticity, genes, and gene-environment interactions. It emphasizes the complexity and nonlinearity of such interplay, illustrated by a survey of anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 188 publications
(147 reference statements)
1
27
0
2
Order By: Relevance
“…Yet, these latter functions do not primarily rely on NMDAreceptor mediated neural transmission (Kalueff, 2007). It may therefore be assumed that the specific dependence of the MMN on the corticostriatal NMDA system underlies this dissociation of performance in HD as well as the enhancement and acceleration of the MMN.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these latter functions do not primarily rely on NMDAreceptor mediated neural transmission (Kalueff, 2007). It may therefore be assumed that the specific dependence of the MMN on the corticostriatal NMDA system underlies this dissociation of performance in HD as well as the enhancement and acceleration of the MMN.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting feature that also differentiates the behavioral profile of the two lines is markedly higher sensation (novelty/reward) seeking behavior in RHA/Verh rats associated with higher motor activity, exploration, drug and alcohol consumption, and impulsivity (Fernán-dez-Teruel et al 1992;Siegel et al 1993;Driscoll et al 1998;Guitart-Masip et al 2006). A growing body of data indicate also that Roman rats display line dependent differences in functional properties of brain neurotransmitters such as 5HT, DA, and GABA (Driscoll et al 1983;Giorgi et al 1994;Giorgi et al 1997;Corda et al 1997;Giorgi et al 2003a, b;Guitart-Masip et al 2006, known to be involved in the control of emotions (Kalueff 2007). Moreover, Guitart-Masip et al (2006 have shown that divergent substance-seeking profiles of these rats result from distinct pattern of D1 and D3 receptor binding and different expression profiles of proteins involved in dopaminergic transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The glutamatergic system has been proven to regulate anxiety disorders in previous studies (Kalueff, 2007;Nair and Singh Ajit, 2008). The NMDA receptors antagonist MK-801 has been shown to exert anxiolytic-like effects in the first trial of an EPM test in a dose-dependent manner, and this effect can be potentiated by diazepam (Sharma and Kulkarni, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between dopamine receptors and OTT is not well-known. Animals with bilateral lesions in the dorsal hippocampus show persistent, enhanced exploration of the open arms during the repeated EPM test with seven-day intervals (da Cruz e Alves-de- Moraes et al, 2013), suggesting that the hippocampus is involved in OTT and the possible existence of mechanisms facilitating the memory-anxiety interplay, including brain neurochemistry and neural circuitry (Kalueff, 2007;Budzynska et al, 2012). However, the role of hippocampal dopamine receptors in OTT is still unclear.…”
Section: Introductionmentioning
confidence: 99%